A new Himalayan species of Alfieriella (Coleoptera: Cryptophagidae) - Chen, Yan-Dong; Leschen, Richard A.b.; Bai, Ming; Yang, Xing-Ke (Zootaxa, 2020)
A new species of Alfieriella Wittmer, 1935 (Coleoptera, Cryptophagidae), Alfieriella senguptai sp. n. from China and India, is described. This is the first formal record of the genus Alfieriella and the tribe Hypocoprini from the Himalayan region. Alfieriella senguptai is the largest member of Alfieriella, and its presence in a cold, high-altitude environment conforms to Bergmann’s rule. The distribution of the genus Alfieriella may be associated with the breakup of the Tethys Ocean and the origin of A. senguptai influenced by the Himalayan orogeny. A distribution map and a key to species of Alfieriella are also provided.